WHO PAYS LESS? CORPORATE INCOME TAX BURDEN OF LISTED CORPORATIONS IN SERBIA AND NORTH MACEDONIA - Vržina, Stefan; Karapavlović, Nemanja (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2022)
Serbia and North Macedonia are two transition countries with relatively low statutory corporate tax rates (STRs) of 15% and 10%, respectively. As tax planning and legal tax avoidance became a factor of corporate competitiveness, it is important to measure and compare corporate tax burden between corporations. Therefore, the main objective of the paper is to calculate and compare corporate tax burden for corporations listed on Belgrade and Macedonian stock exchanges, included in BELEX15 and MBI10 stock exchange indices. On the other side, many measures of corporate tax burden have been developed in the past decades, though the ideal measure of corporate tax burden is yet to be designed. We have calculated effective corporate income tax rates (ETRs), as the most widely used measure of corporate tax burden. ETR is calculated as a relation between current corporate income tax expense and pre-tax profit. We have showed that corporations in Serbia have lower ETRs than corporations in North Macedonia, despite the STR being higher in Serbia. Contrary to the North Macedonian corporations, the difference between ETR and STR is statistically significant in Serbian corporations. However, we argue that ETRs do not enable cross-national comparison of corporate income tax burden when countries impose different STRs. In this regard, we propose several options to overcome such obstacle, but argue that the relation between ETR and STR is the best measure of corporate income tax burden in such environment. We have reached several conclusions and addressed recommendations to many interest groups, though we emphasize the relatively small sample as the largest limitation of our research.
Keywords: Corporation, Corporate tax, Tax avoidance, Effective tax rate, Stock exchange, Transition economies